1998
DOI: 10.1093/ajcp/110.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Interobsenrer Variability of a Papanicolaou Smear Diagnosis of Atypical Glandular Cells of Undetermined Significance

Abstract: A b s t r a c t The interobserver variability of a Papanicolaou smear diagnosis of atypical glandular cells of undetermined significance (AGUS) has not been measured. Four expert cytopathologists restrospectively reclassified 100 smears originally diagnosed as AGUSAlthough the Papanicolaou smear is one of the most effective screening tools in medicine, errors still occur. One source or error that has received a great deal of attention is diagnostic error, which is a leading cause of medical litigation.1-17 The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 9 publications
6
57
0
2
Order By: Relevance
“…Our interobserver statistical data on AGC correlates with that of others including Raab et al [25], Lee et al [26], and Simsir et al [27]; however, these prior studies utilized conventional smears rather than liquid-based preparations. Due to the timing of studies, Raab et al [25] relied on criteria from TBS from 1988, while Lee et al [26] and Simsir et al [27] referenced TBS from 2001.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our interobserver statistical data on AGC correlates with that of others including Raab et al [25], Lee et al [26], and Simsir et al [27]; however, these prior studies utilized conventional smears rather than liquid-based preparations. Due to the timing of studies, Raab et al [25] relied on criteria from TBS from 1988, while Lee et al [26] and Simsir et al [27] referenced TBS from 2001.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the timing of studies, Raab et al [25] relied on criteria from TBS from 1988, while Lee et al [26] and Simsir et al [27] referenced TBS from 2001. In the study by Raab et al [25] with 4 cytopathologist reviewers, there was complete interobserver agreement in only 15% of AGC [25]. In the study by Lee et al [26], 20.3% of AGC were reclassified by at least 1 cytopathologist reviewer [26].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] ratio, nuclear membrane irregularities and presence of single atypical cells. 21 In this study, however, highgrade CIN is not the most common end point in follow-up assessment of AGUS/AGC cases. This may be due to the application of more stringent cytologic criteria in diagnosing glandular lesions in Queen Mary Hospital.…”
Section: Time Interval Between Cytologic Diagnosis Of "Agc" and Detecmentioning
confidence: 62%
“…11,25,27 Hence, AGUS is still considered today "a poorly understood Bethesda System diagnostic category that needs further characterization." 22 Indeed, according to that system, the only quantitative cytologic feature identified for AGUS cases, including AIS, is a nuclear area three to five times larger than normal. 19 However, as has been the case in previous quantitative studies on AIS, 13,29 our morphometric results showed AGUS nuclear area to be only twice that of normal nuclei.…”
Section: Discussionmentioning
confidence: 99%